Touchio: fingertips cover / Eqbal Naqib Elmi-Rizal - Elmi-Rizal, Eqbal Naqib (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Covid 19 is a current disease phenomenon that infected everyone from all over the world. People may also become infected by touching surfaces that have been contaminated by the virus due to this pandemic situation. It is because the virus can survive on hard surfaces from a few hours to a few days. So, I designed a product that prioritized to keep the distance between a person's fingers from touching things. Touchio is a fingertips cover product that come with UV light sterilizer case purposely to keep the fingertips cover clean from the virus after use it. This product itself have a touch screen friendly grip and thin rubber band to fit according to the adult or boomer fingers. This product also switching to a more sustainable lifestyle in the community which is use natural rubber collected from the rubber tree as the cover and have waterproof breathable fabrics part that are made from recycled waste to prevent the person's fingers from sweating. The purpose I designed this product are (1) to create a product that use a suitable material to make it easy and comfortable to wear, (2) to design a product that is portable and (3) to improve a product with additional features or functions. The design of the product focuses on the issues that have been found during research process through survey in Google Form that take up by 37 respondents. Most of the respondent's age are around 17-30 years old. This approach is used to acquire relevant information from the respondents regarding the existing handling and passing things product such as glove. Majority of the respondents do not satisfied with the existing handling and passing things product. Therefore, the goal of this survey is to discover the solutions to improve the features and functions of handling and passing things product. According to the findings, it shows that an improvement of handling and passing things product could enhance the ways of using which could make the user's daily life more easier. It could give benefits to the user to overcome their problem such as palm sweating, sticky and difficult when to wear the handling and passing product. The solution is to choose a suitable material, enhance the grip and adding new features and functions on the product itself. I hoped that, with this invention, it can give the user a trust to have desire and bravery to touch things without hesitation again. Other than that, I hoped that it can avoid the virus from spreading to other items or the person themselves and do other activities using this product.